Pola Pendidikan Agama Islam dalam Penguatan Pendidikan Ibadah Masyarakat Lansia di Persulukan Syekh Muhammad Thoib Batu Gajah Kec. Barumun Kab. Padang Lawas - Hasibuan, Fadila; Matsum, Hasan; Z, Zulkipli (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the implementation of Islamic religious education for the elderly community at Persulukan Syekh Muhammad Thoib, Barumun District, Padang Lawas Regency; the pattern of Islamic religious education in strengthening worship education for the elderly community at Persulukan Syekh Muhammad Thoib; and the impact of implementing Islamic religious education patterns in strengthening worship education for the elderly community at the same institution.This research employs a field research design with a qualitative approach. Data were collected through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The techniques used to ensure data validity were extended participation, persistent observation, triangulation, and negative case analysis. The results of the study show that the implementation of Islamic religious education for the elderly community at Persulukan Syekh Muhammad Thoib, Barumun District, Padang Lawas Regency, includes worship guidance (congregational prayers), majelis taklim (religious study groups), tawajjuh (spiritual reflection), and suluk mentoring. The pattern of Islamic education in strengthening worship among the elderly is carried out through elderly-friendly da’wah approaches, interactive and collaborative learning, motivational and spiritual reinforcement, and individual assistance.